2015
DOI: 10.4103/0975-962x.165047
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of surface properties of enamel and different esthetic restorative materials under erosive and abrasive challenges: An in vitro study

Abstract: Introduction:Noncarious tooth surface loss is a normal physiological process occurring throughout the life, but it can often become a problem affecting function, esthetics or cause pain.Aim:The purpose of this study was to assess the effect of erosive and abrasive challenges on the surface microhardness and surface wear of enamel and three different restorative materials, that is, nanofilled composite, microfilled composite and resin-modified glass ionomer cement (RMGIC) by using Vickers microhardness tester a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 25 publications
0
3
0
3
Order By: Relevance
“…It can be attributed to the softening and dissolution of the matrix surrounding the glass particles and could result from the siliceous hydrogel layer’s dissolution. 15 This could result in a rough surface that has increased surface area for the adsorption of pigments, leading to staining. 16 Overall maximum color change was seen in GIC Fuji IX GP Extra compared to Ketac Universal Glass Ionomer restorative.…”
Section: Discussionmentioning
confidence: 99%
“…It can be attributed to the softening and dissolution of the matrix surrounding the glass particles and could result from the siliceous hydrogel layer’s dissolution. 15 This could result in a rough surface that has increased surface area for the adsorption of pigments, leading to staining. 16 Overall maximum color change was seen in GIC Fuji IX GP Extra compared to Ketac Universal Glass Ionomer restorative.…”
Section: Discussionmentioning
confidence: 99%
“…Já as consequências do contato de ácidos com a estrutura dentária ou, por analogia, talvez com materiais restauradores, parecem sofrer influência de uma série de fatores: químicos, biológicos ou comportamentais Eakle, 1984;Kaur et al, 2015;Batista et al, 2016). A avaliação do efeito da ciclagem de pH, com um refrigerante a base de cola, em diferentes materiais restauradores e no esmalte adjacente a cada um desses materiais revelou que o desgaste da estrutura dentária é muito maior que o observado para os tais materiais (Honório et al, 2008), verdade seja dita bem pouco prejudicados caso tal ciclagem não seja prolongada (Francisconi et al, 2008).…”
Section: Discussionunclassified
“…Sugere-se que o sejam quando a perda de estrutura dentária implicar severo comprometimento da anatomia cervical, insatisfação do paciente com o aspecto estético, nicho para retenção de alimentos ou biofilme, danos aos tecidos periodontais, hipersensibilidade dentinária não passível de controle por medidas não ou microinvasivas, e suscetibilidade do remanescente a fratura ou necrose pulpar (Bader et al, 1993;Folwaczny et al, 2000;Ichim et al, 2007b;Kaur et al, 2015;Pecie et al, 2011a;Chee et al, 2012;Guimarães et al, 2014).…”
Section: Tratamento De Lesões Cervicais Não Cariosas Em Forma Deunclassified
See 1 more Smart Citation
“…However, when placed in large restoration or for those patients with bruxism and clenching behavior, the wear of composites may still be a concern. Several studies found that nanofilled composites (Filtek Z350 XT) have high compressive strength, hardness, and greater wear resistance when compared to microfilled composite, resin-modified glass ionomer cement [67] and microhybrid composites. [68,69] However, Yesil et al ( 2008) evaluated the 3-body abrasive wear resistance of nanofilled composite resin (Filtek Supreme), nanohybrid composite (Premise), microfilled composite (Heliomolar RO), and microhybrid composite (Point 4).…”
Section: Properties Of Dental Compositesmentioning
confidence: 99%